Da docência à criação de spin-offs acadêmicos: aspectos que impactam na decisão de levar a pesquisa para o mercado - Igor Augusto de Melo Dias (2018)
This dissertation carried out a qualitative study aiming at identifying factors which influenced the professors and researchers` decisions at Federal University in Minas Gerais state, Brazil (UFMG) to commercially explore the resulting technology of the research done in this institution laboratories. The data were collected initially by means of document analysis in the Transference Coordination and Technological Innovation departments at UFMG. This made it possible to identify 16 spin-off cases created inside the institution with the participation of the professors as partners. Based on this first sample, seven semi-structured interviews with the spin-off founder professors were realized with the purpose of exploring the technology, which they had patented. After the data collecting stage, the interviews were transcribed and the results were properly organized by categories, according to the content analysis methodology proposed by Bardin (2011). The results show that the researchers and professors understand that the entrepreneurship demands knowledge in the management area which they had to get familiar with in order to structuring their own business (entrepreneurship). In addition to that, the data collected show that the interviewees are aware of the fact that the entrepreneurship activities have a high degree of uncertainty and risk. According to the literature, it was possible to identify that the interviewees` formation (doctorate and post-doctorate) took place in an institution with a strong culture (influence) in academic entrepreneurship outside Brazil, which contributed to increase their interest in the possibility to create spin-off. It was also possible to observe that most interviewees are full professors and have written high Impact papers. This stresses the need of an academic excellence in order to form spin-offs. The main motivation to create the spin-offs, based on what the interviewees reported, was the technology diffusion through their commercialization and the possible positive social and economic impacts that the research carried out at the university can have in the population. The financial gains of spin-offs was not one of the main reasons which made the interviewees become entrepreneurs. The research also made it possible to identify the existence of a time conflict in between the activities at university and spin-offs making the participation inside the company very limited. An absence of programs that encourages the academic entrepreneurship focused on professors was also perceived. The interviewees felt insecure concerning the legal norms and the institution itself and the existing limits between the two activities. Finally, it is important to stress that the experiences as entrepreneurs are crucial for the students formation and that the researchers/professors mission was focused on the academy, with the exception of retired professors cases who, at present time, dedicate all their time to the created spin-offs.